olod

20 Reputation

3 Badges

7 years, 226 days

MaplePrimes Activity


These are replies submitted by olod

@tomleslie 

Hello.

I am solving a problem using the homotopy perturbation problem, I have the code already but I don't know how to fix my f0(eta) = 1 - e^-(eta). f0(eta) is the assumed solution. 

Thanks. 

Download TRY.mw

@Kitonum 

Hi,

Can I get the maple modification code.

Thanks for you cooperations.

Cheers.

@tomleslie Thanks for your usual understanding and co-operation. #Cheers.

@tomleslie

Hello.

It gives me a great pleasure to write to you.

How can I generate a table by varying a particular parameter ( P_r) for the dummy u(y,t) at x = 0. 

Thanks. 

@tomleslie Thanks for your consideration and understanding.

See you at the top. Cheers.

@tomleslie Thanks for your consideration.

How can I fixed t (i.e t = 0.2) and then plot a graph of the dependent function against  x, 

i.e u(x,t) against x, dummy(x,t) againt x, w(x,t) against x and the rest. I want a 2d plot all through. 

Once again Gracias!.

 

 

@tomleslie Sorry for the typographical error. What I need is the partial derivative of u(x,t) with respect to x, evaluated at x = 0. Thanks.

@tomleslie 2012, You are quite right, Kindly assign any value to the parameters (e.g D_r, P_r  e.t.c). I have the numerical solution to the problem using THETA METHOD already, my headache is how to obtain the partial derivative of u(x,t) with respect to y since I only have a numerical value for u(x,t), w(x,t) and the rest. Thanks.

 

Ouch, that was an ommission. This is the boundary conditon. : {phi(0, t) = 1, phi(9, t) = 0, phi(x, 0) = 0, u(0, t) = t, u(9, t) = 0, u(x, 0) = 0, w(0, t) = 0, w(9, t) = 0, w(x, 0) = 0, theta(0, t) = 1, theta(9, t) = 0, theta(x, 0) = 0}. Thanks.

PDE := {diff(phi(x, t), t) = (diff(phi(x, t), x, x))/S__c-K__r*phi(x, t)+S__r*(diff(theta(x, t), x, x)), diff(u(x, t), t) = diff(u(x, t), x, x)-M^2*(u(x, t)-m*w(x, t))/(m^2+1)-u(x, t)/`ϰ`-2*Omega^2*w(x, t)+Gr*theta(x, t)+Gm*phi(x, t), diff(w(x, t), t) = diff(w(x, t), x, x)+M^2*(m*u(x, t)-w(x, t))/(m^2+1)-w(x, t)/`ϰ`+2*Omega^2*u(x, t), diff(theta(x, t), t) = lambda*(diff(theta(x, t), x, x))/P__r}

@Carl Love 

Page 1 of 1